Developing PISA-Like Math Tasks on Algebra Using Arabic Contexts - Turidho, Aisyah; Putri, Ratu Ilma Indra; Susanti, Ely; Johan, Mery (Universitas Sriwijaya in collaboration with Indonesian Mathematical Society (IndoMS), 2021)
This development research aimed to develop valid and practical PISA-like math tasks on algebra using Arabic contexts that potentially affect mathematical literacy skills. This research was comprised of two stages, preliminary and formative evaluations. This research employed the lesson study learning community (LSLC) system in the development and implementation process and involved grade eight students aged 13-15 years old in Junior High School 19 Palembang. Data collection techniques were walkthrough, observations, and interviews, while the analysis techniques were tests. This research produced six units and nine items of PISA-like-math problems with the content characteristics using Algebra topic, Arabic personal and social contexts, levels 2, 3, 5 and 6 following the 2018 PISA framework, process competencies at mathematical literacy skills, standard language application, applicability for students, and interpret by students. To conclude, the developed PISA-like math tasks were valid, provided practicality, and potentially affected on mathematical literacy skills, and learning to confront Arabic culture in South Sumatera. DOI: https://doi.org/10.22342/jpm.15.2.14847.203-216